2019
DOI: 10.1080/16078454.2019.1565149
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate logistic analysis of predictors of response to immunosuppressive therapy in children with aplastic anemia: a double-center study

Abstract: Background: Immunosuppressive therapy (IST) composed of antithymocyte globulin (ATG) and cyclosporine A (CSA) is one of the standard therapies in pediatric patients with acquired aplastic anemia (AA), but predictors of IST are lack of consensus. Procedures: Ninety-four patients from two pediatric medical centers in China were included between January 2005 and March 2018. Clinical factors associated with the efficacy were analyzed according to multivariate logistic regression model previously established. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
(54 reference statements)
2
10
0
Order By: Relevance
“…Overall survival in IST studies for SAA in children is usually reported after relatively limited follow‐up, with the notable exception of National Institutes of Health and EBMT series 13‐20 . Here, we report favourable very long outcomes with a median follow‐up of more than 10 years.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Overall survival in IST studies for SAA in children is usually reported after relatively limited follow‐up, with the notable exception of National Institutes of Health and EBMT series 13‐20 . Here, we report favourable very long outcomes with a median follow‐up of more than 10 years.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, we found that only female gender and SAA vs VSAA were additional favourable predictive factors for response to IST, considering limited numbers of patients and the retrospective nature of the study. Other predictive factors of response in children include interval between diagnosis and treatment, telomere length, baseline lymphocyte counts and lymphocyte depletion early after IST 1,13‐15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 It is reasonable to hypothesize that the LY change during IST can predict the IST response rate. Gu et al 43 emphasized the role of the decreased LY rate in the first week after IST in IST efficacy prediction. However, the results of the present study found no significant difference in the decreased LY rate in the first week after IST between the response group and the non-response group.…”
Section: Discussionmentioning
confidence: 99%
“…The number of platelet transfusions has an inverse correlation with outcomes after an immunosuppressive therapy or stem cell transplantation. [ 6 ] The use of topical antifibrinolytic agents such as tranexamic acid is particularly effective and can be administered in the form of soaked gauzes, mouthwash or crushed tablets applied locally. [ 7 ] Up to 80% of patients with aplastic anemia in India can present with minor bleeding, and avoiding unnecessary platelet transfusions can reduce the cost and complications of treatment.…”
mentioning
confidence: 99%